Perlindungan Hukum Hak Waris Anak dari Perkawinan Poligami yang Tidak Dicatatkan (Studi Putusan Mahkamah Agung No. 671K/Ag/2015) - Fitri Ayu Sari Wijaya (DOKTRINA: JOURNAL OF LAW, 2020)
The legal protection for the children from unregistered polygamous marriages can be gained through an application for itsbat marriage or marriage ratification to the Religious Court pursuant to Article 7 paragraph (2) of the Compilation of Islamic Laws. The application is submitted to the Religious Court. By the decree stipulated by the court, the children from the unregistered polygamous marriages will gain legal status as legitimate children. The inheritance right status of the children according to the Compilation of Islamic Laws is granted only to children who have nasab relationship or blood relation with the mother and mother’s family, pursuant to Article 100 of the Compilation of Islamic Laws. The Verdict of the Supreme Court Number 46/PUU-VIII/2010 is resulted from a judicial review to Article 43 of Marriage Act stating that the children from unregistered marriages also obtain the similar inheritance right status as the children from a registered one. The legal consideration of the judge in the Verdict of the Supreme Court Number 671 K/Ag/2015, according to the legal certainty stipulated in the laws, is already right, since it is in line with the provisions in Article 2 paragraph (1) and (2), Article 42 and Article 43 of the Marriage Act due to the absence of the marriage certificate that can prove when the marriages took place. However, the verdict has not fulfilled the justice value of inheritance right of children from the unregistered polygamous marriage